Peningkatan Kompetensi Akademik Guru SMAN 1 Purwosari Kabupaten Pasuruan Melalui Kegiatan Pelatihan dan Pendampingan Metode Project Based Learning dan Problem Based Learning Untuk Mempersiapkan Generasi Abad 21 - Sopiah Sopiah; Handri Dian Wahyudi; Fitriana Fitriana; Etta Mamang Sangadji (Lembaga Pengembangan Kinerja Dosen, 2024)
21st century teachers are required to be professional, required to have a combination of 4 main skills, namely: academic, professional and social skills to educate and teach students effectively and efficiently. Increasing teacher academic competence is very important in supporting students' preparation for the 21st century generation, in addition to other competencies. Academic competency includes mastery of material and how to convey that material effectively and efficiently. This Community Service Activity (PKM) aims to improve teacher academic competence through training and mentoring activities with Project Based Learning (PJBL) and Problem Based Learning (PBL) learning models. The PKM method used is a service learning process. Participants in PKM activities are teachers from SMAN 1 Purwosari, Pasuruan Regency. Data was collected using techniques: observation, interviews, tests and questionnaires. The results of PKM activities show an increase in teacher academic competence regarding 2 learning models (PJBL and PBL). The teacher's response after participating in PKM activities was very good and positive and they even recommended similar activities in 2025.